Effect of metformin on left ventricular mass and functional parameters in non-diabetic patients: a meta-analysis of randomized clinical trials - Ahmed M. Kamel; Nirmeen Sabry; Samar Farid (BMC Cardiovascular Disorders, 2022)
Highlights 1. Metformin therapy regresses LVH by approximately 10 g/m2 in non-diabetic patients after 12 months of use (SMCC = −0.63, 95% CI − 1.23; − 0.04, p = 0.04). 2. Metformin therapy was associated with a modest (2–3%) but greater overall improvement in LVEF. 3. Higher dose (> 1000 mg/day) and longer treatment duration were associated with a significant effect for metformin on LVMI and LVEF. 4. Metformin use in HF patients was associated with an absolute increase of 3.21% in LVEF (SMCC = 0.23; 95% CI 0.1; 0.36, P = 0.004).